2005
DOI: 10.1002/ajmg.a.30834
|View full text |Cite
|
Sign up to set email alerts
|

Cardiofaciocutaneous syndrome (CFC) with congenital peripheral neuropathy and nonorganic malnutrition: An autopsy study

Abstract: Many phenotypic manifestations have been reported in cardiofaciocutaneous (CFC) syndrome, but none, to date, are pathognomonic or obligatory. Previous histopathological studies reported findings in skin and hair; no autopsy studies have been published. We report the clinical and autopsy findings of a 7‐year‐old boy with severe CFC syndrome and malnutrition of psychosocial origin. Manifestations of CFC, reported previously, included macrocephaly and macrosomia at birth; short stature; hypotonia; global developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
(62 reference statements)
2
12
0
2
Order By: Relevance
“…29,41,42 Peripheral neuropathy has been rarely documented in CFC, but may be underdiagnosed. 43,44 Brain MRI studies reveal structural malformations in 9% to 85% of patients with CFC. 42 Abnormalities include ventriculomegaly, hydrocephalus, cortical atrophy, prominent Virchow-Robin spaces, and abnormal myelination.…”
Section: Neurologic Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…29,41,42 Peripheral neuropathy has been rarely documented in CFC, but may be underdiagnosed. 43,44 Brain MRI studies reveal structural malformations in 9% to 85% of patients with CFC. 42 Abnormalities include ventriculomegaly, hydrocephalus, cortical atrophy, prominent Virchow-Robin spaces, and abnormal myelination.…”
Section: Neurologic Findingsmentioning
confidence: 99%
“…[40][41][42] It has been suggested that central nervous system malformations are underreported in CFC because only 38% to 50% of children have had brain MRI or computed tomography scans. 42,44 The fact that many children with CFC do have structural brain malformations suggests the need for brain imaging in patients with CFC, as finding morphologic brain changes could lead to better understanding of the individual' s neurologic findings or underlying diagnosis. For example, individuals with NS have relatively few central nervous system malformations, and a brain MRI with some of the above structural abnormalities may suggest a diagnosis of CFC rather than NS.…”
Section: Neurologic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 There are several case reports where these neurological features are described in patients with CFC; however, there has never been a systematic evaluation of neurological involvement in this condition. [10][11][12][13][14][15] This report describes neurological features of the largest cohort of mutation-positive individuals with CFC reported to date.…”
mentioning
confidence: 97%
“…In a large series of CFC syndrome patients, the percentage of children who have undergone a brain CT or MRI ranges from 38% to 50% [Gross-Tsur et al, 1990;Wieczorek et al, 1997;Manci et al, 2005]. The incidence of structural brain abnormalities in CFC patients who have undergone brain imaging ranges from 9.4-85.7% [Gross-Tsur et al, 1990;Wieczorek et al, 1997;Manci et al, 2005].…”
Section: Discussionmentioning
confidence: 99%